F43 Validity of accelerometers to quantify energy expenditure under controlled conditions for huntington´s disease patients. (12th September 2022) - Simón-Vicente, Lucía; Rivadeneyra-Posadas, Jéssica; Soto-Célix, María; Raya-González, Javier; Castillo-Alvira, Daniel; Calvo, Sara; Collazo, Carla; Rodríguez-Fernandez, Alejandro; Fahed, Vitória S; Mariscal, Natividad; García-Bustillo, Álvaro; Aguado, Laura; et al.
Abstract : Background: Consumer and research activity monitors have become popular because of their ability to quantify energy expenditure (EE) in free-living conditions in a cost-efficient way. However, there is not research on the validity of this devices in people with Huntington's disease (HD). Aims: To determine the accuracy of the Actigraph and Fitbit compared to indirect calorimetry (IC) (Medisoft Ergo Card) to measure EE during treadmill walking. Methods: Fourteen symptomatic ambulatory HD patients (age 57.3 ± 9.9 years) from the Neurology Department of the Burgos University Hospital wore an Actigraph, positioned on the right hip and a Fitbit, on the dominant hand wrist during the test (running on a treadmill at 3.2km/h and 5.2km/h for three minutes in each speed and an incremental test starting at 1.5 km/h with increments of 0.5 each 1-min until subject voluntarily showed exhaustion). Energy expenditure estimates were compared against EE (rate of oxygen consumption) measured by a gas analyzer. Results/Outcome: A significant reliability was found at a speed of 5.2km/h (ICC=0.434) and substantial agreement at the incremental test (ICC=0.709) between Actigraph and IC. The agreement between Fitbit and IC was poor in the overall treadmill walk. The Fitbit significantly overestimated EE compared to IC. Conclusions: This is the first study that provides evidence for the relative validity of the Actigraph (compared to criterion measure) for the estimation of EE in HD patients.